Genomics and transcriptomics reveal β-carotene synthesis mechanism in Dunaliella salina - Chen, Duo; Li, Zhenhui; Shi, Jiaxian; Suen, Huamiao; Zheng, Xuehai; Zhang, Cifeng; Chen, Youqiang; Xue, Ting (Frontiers in Microbiology, 2024)
Dunaliella salina is by far the most salt-tolerant organism and contains many active substances, including β-carotene, glycerol, proteins, and vitamins, using in the production of dried biomass or cell extracts for the biofuels, pharmaceutical formulations, food additives, and fine chemicals，especially β-carotene. We report a high-quality genome sequence of D. Salina FACHB435, which has a 472 Mb genome size, with a contig N50 of 458 Kb. A total of 30,752 protein-coding genes were predicted. The annotation results evaluated by BUSCO was shown that completeness was 91.0% and replication was 53.1%. The fragments were 6.3% and the deletions were 2.6%. Phylogenomic and comparative genomic analyses revealed that A. thaliana diverged from Volvocales about 448 million years ago, then Volvocales C. eustigma, D. salina, and other species diverged about 250 million years ago. High light could promote the accumulation of β-carotene in D. salina at a 13 d stage of culture. The enrichment of DEGs in KEGG, it notes that the predicted up-regulated genes of carotenoid metabolic pathway include DsCrtB, DsPDS, DsZ-ISO, DsZDS, DsCRTISO, DsLUT5, DsCrtL-B, and DsCCD8, while the predicted down-regulated genes include DsCrtF, and DsLUT1. The four genes that were both up-regulated and down-regulated were DsZEP, DsCrtR-b, DsCruA/P and DsCrtZ 4. The research results can provide scientific basis for the industrialization practice of D. salina.